Design and Validation of a Scale for Perception of Key Factors for Workplace Harassment Prevention - Armijos , Juan Carlos; Alvarez-Maldonado, David; Oradini, Nicolas Barrientos; Puentes , Carlos Aparicio; Jara, Victor Manuel Yanez (Journal of Ecohumanism, 2025)
In an increasingly complex work environment, workplace harassment has become a critical issue, affecting both individuals and organizations. This study focuses on the validation of a perception scale for key factors in workplace harassment prevention, developed through exploratory and confirmatory factor analysis, using a sample of 480 individuals, consisting of union leaders and employers. Based on a bibliometric review of the literature, the relevance of addressing this phenomenon from a health perspective is identified. The exploratory factor analysis revealed three fundamental dimensions: institutional, normative, and social aspects, which were confirmed in the subsequent stage with a good model fit. The results highlight the importance of more effective implementation of preventive policies and the need for a proactive approach in identifying workplace harassment, validating a useful tool for evaluating this phenomenon in organizational settings from the perspective of the involved actors. This research contributes to the understanding of workplace harassment, providing a foundation for future interventions and studies in this area.